Strengthening Stunting Prevention Education Based on Local Wisdom for Mothers Under Five in Coastal Areas - Yoga Tri Wijayanti; Yunita Kristina; Ari Setiawati; Viyan Septiyana Achmad; Astuti Astuti (Edukasi Ilmiah Indonesia, 2026)
Introduction: Stunting remains a major public health concern in Indonesia, particularly in coastal communities where socio-cultural factors and limited access to continuous health education influence nutritional practices. Maternal knowledge plays a critical role in shaping child feeding practices and preventing stunting. This study aimed to strengthen stunting prevention education among mothers of children under five through a local wisdom-based approach in a coastal area. Methods: A community-based intervention was conducted on March 5, 2026, involving 35 mothers of children under 5 years old. The program integrated culturally adapted educational materials with participatory learning methods, including interactive sessions, group discussions, and demonstrations. Data were collected using pre-test and post-test questionnaires to assess changes in knowledge. Results: The intervention led to a significant improvement in maternal knowledge. The mean score increased from 56.8 ± 10.4 in the pre-test to 82.3 ± 8.7 in the post-test, with an average increase of 25.5 points. This improvement indicates that the intervention was effective in enhancing understanding of balanced nutrition and appropriate feeding practices. Conclusion: The local wisdom-based educational approach proved effective in improving maternal knowledge related to stunting prevention. Integrating cultural values with evidence-based health education can enhance program acceptance and effectiveness, particularly in coastal communities. This approach has the potential to be adapted and implemented in similar settings to support sustainable stunting prevention efforts.